1962
DOI: 10.1126/science.138.3538.434
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplasts and Mitochondria in Living Plant Cells: Cinephotomicrographic Studies

Abstract: Chloroplasts in situ are surrounded by jackets of a material which does not contain chlorophyll. The chlorophyll-bearing inner structure lacks motion while the jackets constantly change shape. Long protuberances may extend from the jackets into the cytoplasm and may segment into particles that cannot be distinguished from mitochondria. Segmentation and other dynamic characteristics of living plant cells have been recorded on cine film.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
97
0
1

Year Published

1963
1963
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 2 publications
2
97
0
1
Order By: Relevance
“…In cinephotomicrographic and video microscopic studies, chloroplast protuberances have been observed to segment into vesicular structures (Wildman et al, 1962;Gunning, 2005). The release of bodies approximately 1.5 mm in diameter from the ends of stromules has been observed (Gunning, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…In cinephotomicrographic and video microscopic studies, chloroplast protuberances have been observed to segment into vesicular structures (Wildman et al, 1962;Gunning, 2005). The release of bodies approximately 1.5 mm in diameter from the ends of stromules has been observed (Gunning, 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Stromules were first observed in spinach cells (12), and have since been observed in every cell type and land plant species investigated to date (13). Several studies have identified conditions that can induce or decrease stromule formation (14)(15)(16)(17)(18), concluding that stromule frequency can change in response to abiotic stress, phytohormone signaling, and massive disruption of cellular function (e.g., strong inhibition of cytosolic translation or of actin microfilament dynamics).…”
mentioning
confidence: 99%
“…In the living higher plant cell, chloroplasts consist of a grantular, chlorophyllouis, stationary lamellar component suirrounded and, presumably, interpenetrated by a pleomorphic mobile phase containing stroma (4,6,21,22). In chloroplasts viewed in situ by electron microscopy ( 14), the stationary lamellar component together with the mobile phase is enclosed by a structural membrane.…”
mentioning
confidence: 99%
“…Individual chloroplasts cotuld be swollen and contracted repeatedly throtugh as many as 4 cycles. The relationsh p between the capacity for osmotic behavior and chloroplast appearaince in cell extracts is dliscuissed.In the living higher plant cell, chloroplasts consist of a grantular, chlorophyllouis, stationary lamellar component suirrounded and, presumably, interpenetrated by a pleomorphic mobile phase containing stroma (4,6,21,22 …”
mentioning
confidence: 99%
See 1 more Smart Citation